First case of visceral Leishmaniosis/HIV coinfection in Niš - southeastern Serbia - Marjanović G. (Archives of Biological Sciences, 2012)
Visceral leishmaniosis (VL) has emerged as an important opportunistic parasitosis associated with human immunodeficiency virus (HIV) infection. The aim of this paper is to report the first case of Leishmania/HIV coinfection in a patient from Niš (Southeastern Serbia). Microscopical examination of Giemsa-stained bone marrow (BM) smears show the presence of Leishmania spp. amastigotes based on their morphological characteristics. In spite of the parasitological finding, the serological test applied gave negative results. Molecular analyses confirmed the infection and allowed us to identify the leishmania species as Leishmania infantum (100% identity). VL/HIV coinfection has important clinical, diagnostic and epidemiological implications. In fact, the failure of serological tests is expected in this condition, and the application of molecular diagnostics to the blood may offer, apart from an easy and non-invasive diagnostic opportunity, the possibility of warning about the risk of possible nosocomial infections. [Projekat Ministarstva nauke Republike Srbije, br. 41018 and br. 175034]